Écrire l’histoire des femmes musulmanes en Europe du Sud-Est. Archives associatives et trajectoires d’engagement en Bosnie dans la première moitié du xxe siècle - Fabio Giomi (Genre & Histoire)
This article examines the possibilities and limitations of the archives of voluntary associations for writing the history of Muslim women during the first half of the twentieth century. The specific context under scrutiny is Yugoslavia, and more precisely Bosnia-Herzegovina, where public archives hold almost no ego-documents related to Muslim women. To this end, we will investigate three types of sources, highlighting their interest and their specificities: the statutes of voluntary associations, the press and bureau reports. The aim is to show how voluntary associations can be a valuable tool for the history of women and their relationship with the public sphere. In doing so, the article will try to counter the dominant historiographical discourse that considers Muslim women in Yugoslavia as passive, invisible and oppressed until the liberation given to them by the Communist Party after 1945.